Improvement proposal for the reduction of time in reception and picking processes through systematization in a logistics operator - Zavaleta Leon, Diego Joel (2025)
Within the supply chain, every stage of the logistics process plays a vital role—from the start of production to the delivery of the product to the final customer. However, storage management stands out as one of the most critical phases. Inadequate storage practices or poor SKU control can result in substantial financial losses for a company. This scientific article presents a diagnostic analysis of a logistics operator specializing in the distribution and storage of pharmaceutical products. During the evaluation, several weaknesses were identified in the reception and order picking processes. As a result, various tools were implemented to enhance operational efficiency. The study explored key questions such as: What are the determining factors for selecting a logistics process systematization model? And what are the implications and effects of its implementation? The chosen tools included a Warehouse Management System (WMS), barcode technology, handheld devices, and ring scanners. These solutions significantly reduced processing times in the logistics activities under review, leading to a noticeable improvement in productivity. Additionally, the company enhanced its ability to respond to orders more effectively and maintained better SKU control. These improvements were validated through a simulation conducted using the ‘Arena’ software.